Lentinan combined with cisplatin for the treatment of non-small cell lung cancer. Issue 12 (26th March 2021) - Zhao, Chenchen; Yan, Haifeng; Pang, Wentai; Wu, Tong; Kong, Xianbin; Li, Xiaojiang; Liu, Honggen; Zhao, Linlin; Liang, Feng; Jia, Yingjie
Abstract: Background: A growing number of studies suggest that lentinan combined with cisplatin thoracic injection for the treatment of lung cancer is an effective combination of traditional Chinese and Western medicine, which has a continuous and beneficial effect on eliminating clinical symptoms and improving cachexia in lung cancer patients. However, whether this treatment is effective and safe for lung cancer patients or not, evidence supporting the effectiveness and safety of this treatment is still incomplete. Besides, there is lack of systematic review to assess the detailed situation (including risk of bias and methodology) of current related clinical studies. Objective: This study aimed to evaluate the effectiveness and safety of lentinan combined with cisplatin thoracic injection in the treatment of lung cancer. Methods: The major databases (Embase, PubMed, the Cochrane Library, China National Knowledge Infrastructure, Chinese Scientific Journals Database [VIP] Database, Chinese Biomedical Literature Service System [SinoMed], and Wanfang Database) were searched from inception to March 1, 2020. Randomized controlled trials (RCTs) of lentinan combined with cisplatin chest injection on patients with non-small cell lung cancer (NSCLC) were identified. Two assessors reviewed each trial independently. The methodological quality of the eligible studies was evaluated according to the Cochrane Collaboration's tool for assessing risk of bias. Both the data extraction and the literature quality screening evaluation were conducted independently by 2 researchers. Results: Totally 17 clinical RCTs were included in this study, involving 1390 patients. Meta-analysis results showed that the clinical efficacy (risk ratio [RR] = 1.34, 95% confidence interval [CI] 1.21–1.48), effective subgroup analysis (RR = 1.51, 95% CI 1.3–1.77), and quality of life (RR = 1.48, 95% CI 1.27–1.72), the differences are statistically significant. In terms of adverse reactions, mainly related to gastrointestinal reactions and bone marrow suppression, the incidence and degree of adverse reactions of lentinan combined with cisplatin thoracic injection group were lower than those of cisplatin thoracic injection group alone. Conclusions: The current evidence prompted that Lentinan combined with cisplatin in thoracic injection might benefit patients with NSCLC on a certain extent; this systematic review revealed some definite conclusions about the application of Lentinan combined with cisplatin in thoracic injection for NSCLC. Due to the low methodological quality, high risk of bias, and inadequate reporting on clinical data, these results still require verification by a large number of well designed, heterogeneous RCT studies. More rigorous, multicenter, sufficient-sample, and double-blind RCTs are warranted.